2018
DOI: 10.4018/ijkm.2018070106
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Styles, Absorptive Capacity and Firm's Innovation

Abstract: The aim of this article is to investigate the relationship between leadership styles, absorptive capacity and firm's innovation in the Jordanian Pharmaceutical sector. It is a knowledge-intensive industry and one where effective leadership has been very substantial. Findings reveal that transformational leadership style and transactional leadership style are antecedents to absorptive capacity and a firm's innovation. The results confirm a significant and direct relationship between both leadership styles and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 72 publications
0
30
0
Order By: Relevance
“…The Jordanian industrial company sector is considered one of the most active and growing sectors in the Jordanian economy. The Jordanian manufacturing sector is characterized by the prosperity of several industries with a high knowledge intensity, such as the pharmaceutical industry (Yaseen et al, 2018;Yaseen, 2019). The Jordanian manufacturing sector has attracted the attention of managers and specialists to the importance of innovation.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Jordanian industrial company sector is considered one of the most active and growing sectors in the Jordanian economy. The Jordanian manufacturing sector is characterized by the prosperity of several industries with a high knowledge intensity, such as the pharmaceutical industry (Yaseen et al, 2018;Yaseen, 2019). The Jordanian manufacturing sector has attracted the attention of managers and specialists to the importance of innovation.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…competitive advantage in Jordan's manufacturing, which is an important economic sector. Manufacturing sectors are characterized as one of the most competitive and diversified industries in terms of innovation (Al-Omoush et al, 2018), especially because this sector involves several firms within a knowledge-intensive industry (Yaseen et al, 2018).…”
Section: Moderating Role Of Technological Intensitymentioning
confidence: 99%
See 2 more Smart Citations
“…Brand equity is one of the sources for creating a competitive advantage for global companies (Kim et al, 2011). Pharmaceutical companies are considered knowledge-intensive industries (Yaseen et al, 2018), and the brand image and brand equity play a significant role in changing the behaviours related to the purchasing intent of physicians and patients, as previous studies have shown, so brand equity has a big role in increasing companies' sales to achieve market share and increase profit (Jing et al, 2014).…”
Section: Discussionmentioning
confidence: 99%